2022
DOI: 10.1093/schbul/sbac061
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Response in Trials of Negative Symptoms in Schizophrenia: A Critical Reassessment of the Evidence

Abstract: Background Summarizing evidence from clinical trials of patients with schizophrenia with predominant or prominent negative symptoms (NS), a prior meta-analysis reported a large placebo effect in negative symptoms (Cohen’s d = 2.909). Assuming that such an effect was clinically not plausible, we performed a critical re-assessment and an update of the previous results with newly available data from add-on and monotherapy studies. Study Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 38 publications
0
14
2
Order By: Relevance
“…In addition, placebo effects may increase over the years of the study (93), but this phenomenon was not found in our study and in the study by Czobor et al as well. Regarding the relationship between illness duration and placebo effects, although no significant association was found, a negative association has been reported in previous researches (30,81). Several studies have shown that unbalanced randomization could also increase placebo effects (30,94), and this association was not significant in our study.…”
Section: Predictors Of Placebo Effects In Ssdcontrasting
confidence: 73%
See 4 more Smart Citations
“…In addition, placebo effects may increase over the years of the study (93), but this phenomenon was not found in our study and in the study by Czobor et al as well. Regarding the relationship between illness duration and placebo effects, although no significant association was found, a negative association has been reported in previous researches (30,81). Several studies have shown that unbalanced randomization could also increase placebo effects (30,94), and this association was not significant in our study.…”
Section: Predictors Of Placebo Effects In Ssdcontrasting
confidence: 73%
“…Regarding the relationship between illness duration and placebo effects, although no significant association was found, a negative association has been reported in previous researches (30,81). Several studies have shown that unbalanced randomization could also increase placebo effects (30,94), and this association was not significant in our study. Apart from the above factors, several subjective factors also need to be considered.…”
Section: Predictors Of Placebo Effects In Ssdcontrasting
confidence: 73%
See 3 more Smart Citations